2017
DOI: 10.1176/appi.ps.201600192
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Treatment Complexity for Major Depressive Disorder for Inpatients With Comorbid Personality Disorder

Abstract: Personality disorder comorbidity made MDD treatment more complex, and recurrence of MDD episodes and hospital readmission occurred more often than if patients had a sole MDD diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
2
8
0
2
Order By: Relevance
“…Future research is needed to further elucidate the relationship and mechanism. According to our results and the previous evidence we reviewed, the presence of a personality disorder is not only associated with depression severity, but the comorbidity of a personality disorder can complicate treatment and worsen the prognosis of depression (Wiegand & Godemann, 2017;Zimmerman, Rothschild & Chelminski, 2005) and other unhealthy outcomes, including self-harming behaviors (Ayodeji et al, 2015). Therefore, understanding the relationship between personality disorders and depression has clinical importance for prognostic accuracy and individualized interventions for depression.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Future research is needed to further elucidate the relationship and mechanism. According to our results and the previous evidence we reviewed, the presence of a personality disorder is not only associated with depression severity, but the comorbidity of a personality disorder can complicate treatment and worsen the prognosis of depression (Wiegand & Godemann, 2017;Zimmerman, Rothschild & Chelminski, 2005) and other unhealthy outcomes, including self-harming behaviors (Ayodeji et al, 2015). Therefore, understanding the relationship between personality disorders and depression has clinical importance for prognostic accuracy and individualized interventions for depression.…”
Section: Discussionsupporting
confidence: 54%
“…For example, compared to patients with major depression, patients with both borderline personality disorder and major depression have poor self-regulation ability, which affects their treatment (Kim et al, 2018). A comorbidity of a personality disorder makes the treatment of major depression more complex, and it is associated with higher rates of recurrent depression and hospital readmission, compared to patients who only have major depression (Wiegand & Godemann, 2017). Personality disorders are also associated with significantly greater severity of self-harm, overall psychopathology, and impairment (Ayodeji et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Looking at healthcare utilization, patients with PD had more psychiatric inpatient, outpatient, and pharmacological treatment than patients with MDD as a single diagnosis [ 22 ]. Additionally, patients with MDD and comorbid PD were more likely to have hospitalizations, higher rates of recurrent depressions, longer mean length of stay [ 23 ], and longer duration of depressive episodes than patients with MDD without comorbid PD [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study published in 2017, Wiegand et al evaluated a large set of data, including 58,913 cases from 75 hospitals using the German VIPP data set. The authors concluded that co-occurring PDs significantly increased the complexity of treating MDD, increased risk of recurrence of MDD, and led to nearly twice as many readmissions within 1 year [12]. This descriptive analysis of a large data set concluded that in this sample, PDs are a significant factor affecting the prognosis in MDD and require significantly increased resources to treat.…”
Section: Recent Evidence Regarding the Impact Of Pds On The Prognosis And Course Of Mddmentioning
confidence: 95%